2011
DOI: 10.1107/s1600536811028170
|View full text |Cite
|
Sign up to set email alerts
|

2-(2-Chloro-6,7-dimethylquinolin-3-yl)-2,3-dihydroquinolin-4(1H)-one

Abstract: In the title mol­ecule, C20H17ClN2O, the dihedral angle between the mean plane of the quinoline ring system and the benzene ring of the dihydro­quinolinone moiety is 57.84 (8)°. In the crystal, mol­ecules are linked into centrosymmetric dimers via pairs of inter­molecular N—H⋯N hydrogen bonds. These dimers are further stabilized by weak π–π stacking inter­actions between pyridine rings with a centroid–centroid distance of 3.9414 (12) Å.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2012
2012
2014
2014

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 19 publications
1
8
0
Order By: Relevance
“…For the synthesis and applications of similar structures, see: Montalban (2011); Wang et al (2011); Nilsson et al (2008); Elliott et al (2006); Metallidis et al (2007); Kaila et al (2007). For related structures, see: Abdel-Wahab et al (2012); Benzerka et al (2011Benzerka et al ( , 2012Benzerka et al ( , 2013. For our previously work on the imidazol unit, see: Bouraiou et al (2011); Hayour et al (2011); Benzerka et al (2012).…”
Section: Related Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…For the synthesis and applications of similar structures, see: Montalban (2011); Wang et al (2011); Nilsson et al (2008); Elliott et al (2006); Metallidis et al (2007); Kaila et al (2007). For related structures, see: Abdel-Wahab et al (2012); Benzerka et al (2011Benzerka et al ( , 2012Benzerka et al ( , 2013. For our previously work on the imidazol unit, see: Bouraiou et al (2011); Hayour et al (2011); Benzerka et al (2012).…”
Section: Related Literaturementioning
confidence: 99%
“…These derivatives were found to be useful biological targets, and at present they attained much attention in the development of new drugs (Metallidis et al, 2007;Kaila et al, 2007). Following of our previous works related to the use of substituted 2-chloro-3-formylquinolines as precursors of different quinoline-containing heterocycles (Bouraiou et al, 2011;Hayour et al, 2011), we have recently reported preparations and antibacterial screening of series of compounds carrying diverse functionalities such as an amine, amide, ester group, heterocylic unit linked to the 2-phenylquinoline entity (Benzerka et al, 2011(Benzerka et al, , 2012(Benzerka et al, , 2013. We report herein the synthesis and single-crystal X-ray structure of 7-methoxy-2-phenylquinoline-3-carbaldehyde (I).…”
Section: Data Collectionmentioning
confidence: 99%
“…For background to and chemical reactivity of quinolone heterocycles, see: Diesbach & Kramer (1945); Prakash et al (1994); Singh & Kapil (1993); Kalinin et al (1992); Chauvin & Olivier (1996). For related structures, see: Bouraiou et al (2008Bouraiou et al ( , 2011; Benzerka et al (2011); Chelghoum et al (2012). Hydrogen-bond geometry (Å , ).…”
Section: Related Literaturementioning
confidence: 99%
“…For previous work on molecules with a quinolyl moiety, see: Benzerka et al (2011); Belfaitah et al (2006) Bouraiou et al (2008Bouraiou et al ( , 2011; Ladraa et al (2009). For applications of pyrazole and its derivatives, see: Mali et al (2010); Paul et al (2001).…”
Section: Related Literaturementioning
confidence: 99%
“…Therefore, studies of the metal complexes are important in the search for new drugs. In previous works, we were interested in the design and synthesis of new molecules that contain a quinolyl moiety (Belfaitah et al, 2006;Bouraiou et al, 2008Bouraiou et al, , 2011Ladraa et al, 2009 andBenzerka et al, 2011). In this paper, we report the structure determination of compound resulting from an unwanted reaction of the 6-methoxy-1H-pyrazolo[3,4b]quinoline with RuCl 3 in acidic conditions.…”
Section: Sup-1mentioning
confidence: 99%